2016
DOI: 10.18632/oncotarget.13340
|View full text |Cite
|
Sign up to set email alerts
|

An early-screening biomarker of endometrial carcinoma: NGAL is associated with epithelio-mesenchymal transition

Abstract: neutrophilgelatinase-associated lipocalin is currently one of the most interesting and enigmatic proteins involved in the development of malignancies. In this study, we found that the expression of neutrophilgelatinase-associated lipocalin was up-regulated in endometrial cancer tissues and cell lines, significantly increased in early-grade ones, suggesting it may serve as a biomarker for early-stage screening for endometrial carcinoma. Moreover, neutrophilgelatinase-associated lipocalin was up-regulated in Ish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
(47 reference statements)
1
5
0
Order By: Relevance
“…In epithelial cells from nasal polyps in CRS, an opposite trend of E-cadherin and N-cadherin expression was identified [20], which was consistent with our finding that miR-761 downregulated N-cadherin but upregulated E-cadherin. In addition, a recent report showcased that the downregulation of E-cadherin and upregulation of vimentin were related to the elevation of neutrophil gelatinase-associated lipocalin [30], which was in line with our results that the depletion of LCN2 led to an increase in E-cadherin and reduced vimentin. LCN2 has been previously shown to reversely regulate EMT via the LCN2/Twist signaling pathway in hepatocellular carcinoma [18].…”
Section: Discussionsupporting
confidence: 92%
“…In epithelial cells from nasal polyps in CRS, an opposite trend of E-cadherin and N-cadherin expression was identified [20], which was consistent with our finding that miR-761 downregulated N-cadherin but upregulated E-cadherin. In addition, a recent report showcased that the downregulation of E-cadherin and upregulation of vimentin were related to the elevation of neutrophil gelatinase-associated lipocalin [30], which was in line with our results that the depletion of LCN2 led to an increase in E-cadherin and reduced vimentin. LCN2 has been previously shown to reversely regulate EMT via the LCN2/Twist signaling pathway in hepatocellular carcinoma [18].…”
Section: Discussionsupporting
confidence: 92%
“…NGAL, a NET-associated protein, is known to promote EMT. 129 The mechanisms involved in the development of subtarsal fibrosis in ocular GVHD have not fully been defined. Because transforming growth factor beta (TGF-β) is known to cause fibrosis, we analyzed the levels TGF-β in ocular surface washings and NETs.…”
Section: Light (Tnfsf14)mentioning
confidence: 99%
“…The clinical significance of measuring NGAL has also been recently highlighted in conditions other then AKI, such as acute bacterial meningitis [10] and bacterial peritonitis [11] . Notably, a growing number of studies have reported that NGAL may be used as an efficient biomarker for early diagnosis and predicting the clinical outcome of certain types of cancer [12] , [13] , [14] .…”
Section: Introductionmentioning
confidence: 99%